An Examination of the Operating Efficiency of Three Financial Intermediaries - Burns, Joseph M. (Journal of Financial and Quantitative Analysis, 1970)
This paper examines the operating efficiency of three types of financial intermediaries in the United States: (1) credit unions, (2) savings and loan associations, and (3) mutual savings banks during the past three decades. In particular, it examines by how much, if any, the operating efficiency of these intermediaries has been enhanced.